Immunoregulatory Effect of Preventive Supplementation of Omega-3 Fatty Acid in a Complex Regional Pain Syndrome Type I Model in Mice - Fernandes, Paula Franson; Galassi, Taynah de Oliveira; Horewicz, Verônica Vargas; Salgado, Afonso Shiguemi Inoue; Mack, Josiel Mileno; Baldança, Heloiza dos Santos; Ferreira da Silva, Ana Paula; Bruehl, Stephen; Bittencourt, Edsel B.; Seim, Lynsey A.; Martins, Daniel Fernandes; Bobinski, Franciane (Frontiers in Integrative Neuroscience, 2022)
Objective Complex regional pain syndrome (CRPS) is usually triggered by trauma or a surgical procedure, and it typically becomes an established one after an intense inflammatory process with chronic pain and edema as the main symptoms. Available treatments for CRPS have low efficacy. This study aimed to evaluate the clinical and immunoregulatory effects of omega-3 polyunsaturated fatty acid (PUFA) supplementation on paw edema and anti- and pro-inflammatory cytokines and macrophage phenotypes in the chronic post-ischemia pain (CPIP) preclinical model of CRPS-Type I. Methods Female Swiss mice were supplemented with omega-3, corn oil, or saline and then submitted to the CPIP model of ischemia/reperfusion (I/R) injury. Supplementation was carried out for 30 days prior to and up to 2 or 15 days after the induction of CPIP, according to experimental protocols. The supplementation protocol included 1,500 mg/kg of omega-3 or corn oil through an intragastric route (gavage). Paw edema, interleukin- (IL-) 4, IL-10, transforming growth factor-β1 (TGF-β1), monocyte chemotactic protein-1 (MCP-1), and tumor necrosis factor (TNF) were then measured in the paw skin and muscle by enzyme-linked immunosorbent assay (ELISA), and macrophage phenotypes (M1 and M2) assessed in the paw muscle by Western blotting. Results The CPIP model induced an increase in paw thickness up to 72 h post-I/R. Mice supplemented with omega-3 compared to the saline group displayed reduced edema but neither altered skin IL-4 or skin and muscle TGF-β1, TNF, and MCP-1 concentrations, nor did they exhibit significantly altered muscle macrophage phenotype on the 2nd-day post-CPIP. However, omega-3 supplementation reversed the I/R-related reduction in IL-4 in the paw muscle compared to groups supplemented with saline and corn oil. Furthermore, omega-3 promoted the reduction of IL-10 levels in the paw skin, compared to animals with lesions supplemented with saline, until the 2nd-day post-CPIP. On the 15th day post-CPIP, IL-10 was significantly increased in the muscle of animals supplemented with omega-3 compared to the saline group. Conclusion The results suggest that omega-3 PUFA supplementation has anti-inflammatory effects in the CPIP model of CRPS-Type I, significantly reducing paw edema and regulating concentrations of anti-inflammatory cytokines, including IL-4 and IL-10.